Evaluasi Tingkat Kematangan e-Government Pada Partisipasi Masyarakat dan Pelayanan Publik Menerapkan Framework Gartner - Muhammad Miftahul Akbar; Wing Wahyu Winarno; Kholid Haryono (STMIK Budi Darma, 2021)
E-government as part of internet products has become a topic of discussion in internet and mass media discussions and is popular after being linked to the regional autonomy policy of districts / cities in Indonesia. However, there are still many government information systems that are developed and implemented that do not function optimally at both the regional and central government levels. Measuring the level of E-government maturity is needed to determine the extent to which the successful application of E-government is. The purpose of the E-government maturity assessment is to provide basic data, advanced data, and all that is necessary for the development of an E-government strategy. Gartner is one of the models used to measure the maturity level of e-government. Gartner's model suggests four critical phases of the evolution of e-government, namely: web presence, interaction, transactions, and transformation. The gartner model is used to measure the maturity level in Sukoharjo district. The research methodology used a questionnaire and the calculation used the average score for each dimension. To determine the relationship between dimensions and criteria, the PLS (Partial Least Square) method is used. Research has proven that the maturity level of E-government is 4.06 (predictable process). The dimensions of transformation and usability affect community participation using e-government in Sukoharjo district.